Улучшение экологии г.Алматы при использовании ГТУ - Тютебаева , Г.М.; Алдиярова, А.Н. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2022)
Улучшение экологии г.Алматы при использовании ГТУ